Relevance of the Use of Video Conferences as a Teaching Resource in the Department of Philosophy at Universidad Estatal a Distancia, Costa Rica - Villalobos Paniagua, Ricardo Antonio (2013)
This article aims to show the results of a research project carried out by the author in order to obtain his Master's Degree in University Teaching from “Universidad Nacional.” This study intended to know and assess the role of a highly relevant and pertinent audiovisual resource in distance education, namely, video conferencing in a particular academic space, Distance State University of Costa Rica (UNED, for its acronym in Spanish) in the Chair of Philosophy that belongs to the School of the Humanities.